Kidney transplantation is associated with reduced myocardial fibrosis. A cardiovascular magnetic resonance study with native T1 mapping - Contti, Mariana Moraes [UNESP]; Barbosa, Maurício Fregonesi; Del Carmen Villanueva Mauricio, Alejandra [UNESP]; Nga, Hong Si [UNESP]; Valiatti, Mariana Farina [UNESP]; Takase, Henrique Mochida [UNESP]; Bravin, Ariane Moyses [UNESP]; De Andrade, Luis Gustavo Modelli [UNESP] (Elsevier, 2019)
Background: The measurement of native T1 through cardiovascular magnetic resonance (CMR) is a noninvasive method of assessing myocardial fibrosis without gadolinium contrast. No studies so far have evaluated native T1 after renal transplantation. The primary aim of the current study is to assess changes in the myocardium native T1 6 months after renal transplantation. Methods: We prospectively evaluated 44 renal transplant patients with 3 T CMR exams: baseline at the beginning of transplantation and at 6 months after transplantation. Results: The native T1 time was measured in the midventricular septum and decreased significantly from 1331 ± 52 ms at the baseline to 1298 ± 42 ms 6 months after transplantation (p = 0.001). The patients were split into two groups through a two-step cluster algorithm: In cluster-1 (n = 30) the left ventricular (LV) mass index and the prevalence of diabetes were lower. In cluster-2 (n = 14) the LV mass index and diabetes prevalence were higher. Decrease in native T1 values was significant only in the patients in cluster-1 (p = 0.001). Conclusions: The native myocardial T1 time decreased significantly 6 months after renal transplant, which may be associated with the regression of the reactive fibrosis. The patients with greater baseline LV mass index and the diabetic group did not reach a significant decrease in T1.
Keywords: Cardiovascular magnetic resonance imaging; Fibrosis; Kidney transplantation; Native T1